HUBUNGAN ANTARA PEKERJAAN, PENDAPATAN, PENGETAHUAN SIKAP LANSIA DENGAN KUNJUNGAN KE POSYANDU LANSIA - Sulistiyawati, Ika (STRADA : Jurnal Ilmiah Kesehatan, 2012)
Elderly is someone who is aged 60 years or more and is the final stage of the life cycle of a normal developmental stage that will be experienced by each individual. The general objective is to enhance the formation of Posyandu Elderly health status and quality of life for the elderly to achieve a happy old age and the powerful in society and family life in accordance with the existence. But the group of elderly themselves less able to take advantage of Posyandu Elderly. This research aimed to analyze the relationship between employment, income, knowledge and attitudes of elderly towards Posyandu Elderly activity of visits to the Primary Health Care (PHC) Sumbersari Jember Regency. The research method used is analytical, cross sectional design, which used quantitative approaches. The sample size in this study were 192 elderly in the work area of the Sumbersari Public Health Center) and use proportional random sampling technique.The result of study shows that the characteristics of the Elderly in the Sumbersari Public Health Center Jember Regency mostly female, medium education, age 45-59 years of age, marital status (a partner), does not work, and income <UMK (The Regional Minimum Wage). Most of elderly the knowledge level about Posyandu Elderly is medium, has a high attitude about Posyandu Elderly, and the frequency of visits to Posyandu Elderly is not active. Work and attitudes of elderly associated with the activity visits to Posyandu Elderly. Whereas knowledge and income unrelated to the liveliness of a visit to the Posyandu Elderly.